Immunomodulatory effects of yogurt as a functional food: Enhancing innate immunity against influenza virus infection through in vivo analysis - Nuramalia, Dwiarti Rachma (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Influenza is a severe respiratory illness that affects people practically everywhere and is brought on by influenza viruses. Although vaccination is often used to prevent influenza virus infection, it is not always effective due to the fast rate of viral mutagenesis and the annual shift in the dominant virus strains. Boosting nonspecific innate immunity is another method of preventing influenza virus infection by strengthening natural defenses. Yogurt and other fermented functional foods have been shown to contribute to health maintenance. Methods: The objective of this review of these studies is to investigate and comprehend the in vivo approach to testing yogurt—a functional food—as an immunomodulator, particularly in influenza infection. Findings: Because extracellular polysaccharides in yogurt influence the immune system and provide protection against IAV infection, it does have immunomodulatory qualities. Yogurt eating on a daily basis before to infection significantly enhanced the survival rate of mice, the cytokine response in the lungs, and NK cell activity. It has been demonstrated that the ingredients in yogurt cause mice's splenocytes to produce more IFN-γ. Conclusion: Yogurt supplemented with nF1 has preventive and protective effects against IAV infection and can trigger immune responses by enhancing NK cell activity. Novelty/Originality of This Study: The novelty of this study lies in its exploration of yogurt as a functional immunomodulator, highlighting its role in enhancing innate immunity and providing protection against influenza virus infection through in vivo analysis.